(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The German language occupies an important position worldwide and is used in numerous social, economic, scientific and cultural areas. This thesis comprehensively examines the use of the German language in various sectors and sheds light on its function as a means of communication, scientific language and cultural carrier. Particular attention will be paid to the influence of globalisation, digitalisation and international cooperation. The aim is to present the relevance of the German language in the 21st century in a differentiated way and to show perspectives for its future development.